Inspiring Leadership Dalam Membangun Organizational Citizenship Behavior (OCB) di Pondok Pesantren - Hikmatul Hidayah; Hasan Baharun (Aafiyah: Jurnal Multidisiplin Ilmu, 2023)
Organizational citizenship behavior, the prosocial attitude of employees/ organizational members mobilized by the leader, is expected to promote effective organizational functioning, so it is the task of the leader to motivate and inspire employees to be willing to do tasks outside the job description. This is an organizational problem that leaders must be able to handle, with some promising (good) employees leaving their jobs, and some employees who stay but with minimal performance because they have no better alternative. This study aims to explain the steps or efforts of leaders to apply inspiring leadership in building organizational citizenship behavior in Islamic boarding schools. This research uses a qualitative approach using the natural environment as a direct data source, with data collection techniques through literature studies and documents and structured interviews. Data analysis techniques by collecting data, reducing or sorting data, exposing data, drawing conclusions, and verifying the validity of data using triangulation techniques. Research findings show that leaders' efforts to apply Inspiring Leadership in Building Organizational Citizenship Behavior (OCB) in Islamic boarding schools are: taking initiatives, strengthening organizations, acting as role models, and visionaries, building strong and productive communication, developing potential, collaborative practices, and teamwork, building emotional relationships, and innovation. Keywords: Inspiring Leadership, Organizational Citizenship Behavior (OCB)